Role of the ACE2/Angiotensin 1–7 axis of the Renin-Angiotensin System in Heart Failure - Patel, Vaibhav B. (Circ Res, 2016)
Heart failure remains the most common cause of death and disability, and a major economic burden, in industrialized nations. Physiological, pharmacological, and clinical studies have demonstrated that activation of the renin-angiotensin system is a key mediator of heart failure progression. Angiotensin converting enzyme 2 (ACE2), a homologue of ACE, is a monocarboxypeptidase that converts angiotensin II (Ang II) into angiotensin 1–7 (Ang 1–7) which, by virtue of its actions on the Mas receptor, opposes the molecular and cellular effects of Ang II. ACE2 is widely expressed in cardiomyocytes, cardiofibroblasts, and coronary endothelial cells. Recent preclinical translational studies confirmed a critical counter-regulatory role of ACE2/Ang 1–7 axis on the activated renin-angiotensin system that results in heart failure with preserved ejection fraction. While loss of ACE2 enhances susceptibility to heart failure, increasing ACE2 level prevents and reverses the heart failure phenotype. ACE2 and Ang 1–7 have emerged as a key protective pathway against heart failure with reduced and preserved ejection fraction. Recombinant human ACE2 has been tested in phase I and II clinical trials without adverse effects while lowering and increasing plasma Ang II and Ang 1–7 levels, respectively. This review discusses the transcriptional and post-transcriptional regulation of ACE2 and the role of the ACE2/Ang 1–7 axis in cardiac physiology and in the pathophysiology of heart failure. The pharmacological and therapeutic potential of enhancing ACE2/Ang 1–7 action as a novel therapy for heart failure is highlighted.